The CADDP 10 per cent target - Still pursued by African leaders? - Benin, Samuel (DLG-Verlag GmbH, 2022)
The 2003 Maputo Declaration aimed at boosting African agriculture requires governments to make difficult decisions on budget priorities. Furthermore, tracking the progress of the initiative presents problems. Our author looks at these and other challenges the Maputo Declaration is facing. And against the background of a continuing decline in government expenditure on agriculture on the continent, he argues that new evidence on expenditure outcomes is required to get governments to reverse the trend.